A foreign body in the cephalic vein: A case report. Issue 25 (June 2018) - Song, Mingzhi; Wei, Maohua; Song, Ze; Li, Liang; Fan, Jifeng; Liu, Mozhen
Abstract: Rationale: Foreign bodies in the vasculature usually cause numerous problems for clinical physicians. Physician experience with diagnosing and treating non-iatrogenic foreign body migration in the venous system is insufficient. Patient concerns: Here, we reported a 41-year-old male who had a foreign body in his left forearm following a work-related injury. Diagnoses: X-ray films indicated a 3-mm high-density shadow in the superficial soft tissue of the left forearm. During the operation, the foreign body was imaged by a C-arm fluoroscope to provide a more accurate location. Interventions: The foreign body was removed completely following a microsuture of the cephalic vein. Outcomes: The procedure was uneventful, and the patient remained asymptomatic after 6 months of clinical follow-up. Lessons: This case indicated that the foreign body in the superficial tissue needed to be accurately diagnosed and located. X-ray and C-arm fluoroscope imaging should be combined with the patient's medical history to ensure sufficient preoperative preparation. Abstract : Supplemental Digital Content is available in the text